The role of good corporate governance in moderating factors affecting tax avoidance - Widitha Puteri Wadana; Atma Hayat; Monica Rahardian Ary Helmina (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of firm size, leverage, and good corporate governance on tax avoidance in manufacturing companies listed on the IDX. This research seeks to utilise firm size, leverage, and GCG to prevent corporate tax fraud since incidents of tax avoidance are on the increase, particularly for businesses listed on the IDX. This type of research is quantitative causal comparative. The sample in this study are 62 companies listed on the IDX in 2016-2021.The analytical method used is Moderate Regression Analysis (MRA). The results of the study conclude that: (1) firm size has a significant effect on tax avoidance (Janrosl & Efriyenti, 2018), (2) leverage has no significant effect on tax avoidance (Rahmadani et al., 2020), (3) firm size has a significant effect on tax avoidance moderated by good corporate governance, (4)leverage has no effect significant effect on tax avoidance moderated by good corporate governance.